The Effect of Religious Extracurricularon Students' Spiritual and Social Attitudes at School - Lahmi, Ahmad; Halim, Syaflin; Novigator, Hendri (LETIGES, 2025)
The present study aims to analyse the influence of religious extracurricular activities on students' spiritual and social attitudes in the school environment. The present study adopts a quantitative research approach, utilising primary data sources. The data were collected using a questionnaire designed to address the research questions in a relevant manner. The questionnaire was disseminated through two methods: online using Google Forms and directly to respondents at school. The stratified random sampling technique selected 123 respondents from grade III students at Padang Vocational High School. The data analysis technique employed in this study utilised SPSS software version 24, encompassing classical assumption tests and hypothesis tests. The results of this study revealed two main findings: Firstly, the findings indicated that religious extracurricular activities significantly influence students' spiritual attitudes, with a significance value of 0.048. Secondly, the results showed that religious extracurricular activities also considerably influence students' social attitudes, with a significance value of 0.033. The originality of this research lies in its exploration of the social dimensions that emerge from religious extracurricular activities, a facet that has been under-explored in the existing literature. This study addresses this gap by incorporating spiritual and social attitudes as dependent variables, thus comprehensively exploring the phenomenon.